Thin and hermetic packaging process for flat panel display application - Kim, Y.; Jeong, J.; Lee, D.; Choi, W.; Lee, S.; Ju, B. (2002)
This paper presents a study on the tubeless Plasma Display Panel (PDP) packaging using glass-to-glass electrostatic bonding with intermediate amorphous silicon. The bonded sample sealing the mixed gas with three species showed high strength ranging from 2.5 MPa to 4 MPa. The glass-to-glass bonding for packaging was performed at a low temperature of 180 °C by applying bias of 250 V in ambient of mixed gases of He-Ne(27 %)-Xe(3 %). The tubeless packaging was accomplished by bonding the support glass plate of 30 mm×50 mm on the rear glass panel and the capping glass of 20 mm×20 mm. The 4-inch color AC-PDP with thickness of 8 mm was successfully fabricated and fully emitted as white color at a firing voltage of 190V. ？ 2002 Taylor & Francis Group, LLC.